Risk Disclosure Research Trends: Bibliometric Evaluative Study - Ag, Kaifah Riyard; Noor Azli bin Ali Khan, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The recent financial crisis has triggered tremendous awareness of the reliability of company financial reports as the main source of information to the market. Poor risk disclosure by the company worsens the situation, as the company may hesitate to disclose disadvantageous information to the market, fearing it will affect the company’s performance. Therefore, further understanding the topic and widening the network are important to developing comprehensive research on the effect of risk disclosure. This bibliometric analysis study was aimed at evaluating global research trends in the risk disclosure area based on the outputs of publications, authors co-authorship and affiliated countries, and authors co-occurring keywords. By using the Scopus database as the main search engine, a total of 400 articles published between 1978 and 2018 were extracted. Based on the analysis, the result suggested that risk disclosure has started getting attention from 2010. The result also highlighted that English is the main language used by the authors in writing articles, followed by German and Spanish It also documented that most of the risk disclosure study came from the United Kingdom and Australia, with a total publication of 18%, superior to the other countries. The study also identified the most popular of sub-research themes for risk disclosure as cost of capital and bank disclosure.